Update on poly(ADP-ribose) polymerase inhibitors resistance in ovarian cancer - Dong, Ruihong; Ding, Ting; Li, Zhengyu (Frontiers in Pharmacology, 2023)
Ovarian cancer is one of the most common reproductive system tumors. The incidence of ovarian cancer in China is on the rise. Poly(ADP-ribose) polymerase (PARP) inhibitor (PARPi) is a DNA repair enzyme associated with DNA damage repair. PARPi takes PARP as a target to kill tumor cells, especially for tumors with homologous recombination (HR) dysfunction. Currently, PARPi has been widely used in clinical practice, mainly for the maintenance of advanced ovarian epithelial cancer. The intrinsic or acquired drug resistance of PARPi has gradually become an important clinical problem with the wide application of PARPi. This review summarizes the mechanisms of PARPi resistance and the current progress on PARPi-based combination strategies.